PENGARUH BIAYA PENGIRIMAN DAN ESTIMASI PENGIRIMAN TERHADAP KEPUASAN PELANGGAN PADA PT. LAUTAN BENUA NUSANTARA INDONESIA DI MEDAN - Manurung, Pasquita Patricia; Rangkuti, Sahnan; Firah, Al (Bisnis-Net, 2024)
This research aims to determine the effect of shipping costs and delivery estimates on customer satisfaction at PT. Lautan Benua Nusantara Indonesia in Medan. The number of samples in this research was 150 customers from a total population. Sample selection uses saturated samples. This research method is a quantitative method. The data collection technique uses primary data and secondary data in the form of a questionnaire using a Likert scale. The results of the t test with a value of tcount < ttable (1.230 < 1.655) mean that shipping costs have no effect on customer satisfaction at PT. Lautan Benua Nusantara Indonesia in Medan. The results of the t test with a value of tcount > ttable (6.108 > 1.655) mean that delivery estimates have a positive and significant effect on customer satisfaction at PT. Lautan Benua Nusantara Indonesia in Medan. The results of the F test with a value of Fcount (20.591) > Ftable (3.060) mean that the variables of shipping costs and delivery estimates have a significant effect on customer satisfaction. The calculation results obtained a coefficient of determination of 0.219 (21.9%). Customer satisfaction is influenced by shipping costs and delivery estimates. Meanwhile, the remaining 78.1% was influenced by other variables not studied. The better the goods delivery process, the greater customer satisfaction will be. The process of arriving goods to customers is not optimal and does not match delivery estimates because the means of transportation used are often damaged. Customer satisfaction is closely related to on-time delivery, safety of goods (goods are not reduced, not damaged, not lost, guarantee compensation). However PT. Lautan Benua Nusantara Indonesia in Medan is not optimal enough in managing timeliness and there is no guarantee of compensation.